Pengaruh Corporate Governance, Profitabilitas dan Leverage Terhadap Manajemen Pajak - Bella Krisda Ningsih; Emmiliana Hartanti (UNIVERSITAS KALBIS, 2022)
This study aims to determine the effect of corporate governance, profitability and leverage on tax management. In this study the sample used was manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the period of 2016-2018 with a total population of 193 companies and sample of 66 companies with a purposive sampling technique. This study uses multiple regression with a random effect approach. Tests conducted in this research are descriptive statistical tests, normality tests, multiple regression analysis tests, coefficient of determination tests, simultaneous and partial significant tests.This study uses multiple regression with a random effect approach. The results of this study indicate that corporate governance and leverage have no effect on tax management, while profitability has an effect on tax management.